2011
DOI: 10.1902/jop.2011.100287
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to the Use of Subgingival Controlled‐Release Chlorhexidine Delivery in Chronic Periodontitis: A Randomized Clinical Trial

Abstract: The use of CHX chips before and immediately after SRP improved CAL and reduced the subgingival microorganisms of the red complex in the treatment of chronic periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…We observed significant reductions in the proportion of P. gingivalis and T. forsythia in test sites, complementary to the clinical findings in our study. Our findings are in accordance with the studies of Mizrak et al [22] and Gonzales et al [24], who demonstrated that the adjunctive use of the CHX chip showed positive results with clinical and microbiological parameters in chronic periodontitis patients. Similarly, Kumar et al [25] also suggested that local drug delivery using the CHX chip enhances the benefit of SRP in the treatment of chronic periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…We observed significant reductions in the proportion of P. gingivalis and T. forsythia in test sites, complementary to the clinical findings in our study. Our findings are in accordance with the studies of Mizrak et al [22] and Gonzales et al [24], who demonstrated that the adjunctive use of the CHX chip showed positive results with clinical and microbiological parameters in chronic periodontitis patients. Similarly, Kumar et al [25] also suggested that local drug delivery using the CHX chip enhances the benefit of SRP in the treatment of chronic periodontitis.…”
Section: Discussionsupporting
confidence: 93%
“…Investigators in 6 studies compared the effects of SRP plus the local delivery of chlorhexidine chips with SRP alone on chronic periodontitis. [63][64][65][66][67][68] Four were splitmouth studies, 63,65-67 and 2 were parallel-group studies. 64,68 All but 2 trials 66,67 had small sample sizes (ranging from 12 to 25 participants per group); the larger studies included between 82 and 116 participants per treatment arm.…”
Section: Moderatementioning
confidence: 99%
“…Compared with SRP alone, SRP plus chlorhexidine chips resulted in a 0.40-mm mean gain in CAL (95% CI, 0.24-0.56) ( Figure 6). [63][64][65][66][67][68] We judged the overall level of certainty in the evidence to be moderate on the basis of the evidence profile in Table 3.…”
Section: Moderatementioning
confidence: 99%
“…Also, Paolantonio showed that the adjunctive use of CHX chip with SRP resulted in a clinically meaningful improvement in PPD reduction compared to SRP alone, but no differences were found in BOP, TBC and frequencies of detection of each of the periodontal pathogens. More recently, Gonzales , in a randomized trial, reported that the use of CHX chips before and immediately after SRP improves clinical attachment loss and reduces the subgingival microorganisms of the red complex in the treatment for chronic periodontitis.…”
Section: Discussionmentioning
confidence: 99%